Aortic valve replacement after coronary artery bypass grafting with the in situ right gastroepiploic artery to the occluded right coronary artery using a temporary vein graft for cardioplegia - Yoshifumi Fuke; Toru Yasutsune; Masato Sakamoto (Surgical Case Reports)
Abstract Background The operation of aortic valve replacement (AVR) after CABG is a technically challenging procedure in respect to dissection of living grafts from its surrounding tissue, myocardial protection, and so on, especially that procedure to patients with living in situ functional arterial grafts to occluded native coronary arteries has a special problem in regard to myocardial protection because myocardial blood supply originates from various arteries including the left internal thoracic artery (LITA), the right internal thoracic artery (RITA), and the right gastroepiploic artery (GEA); hence, adequate myocardial protection should be fastidiously considered. Case presentation A 68-year-old woman, who underwent CABG comprised of the in situ LITA to the LAD, the in situ GEA to the RCA, and the saphenous vein graft (SVG) to the obtuse marginal branch of the left circumflex artery (LCX) to the triple vessel coronary disease 9 years before, was referred to our hospital due to the aortic valve stenosis. Conclusion We successfully underwent an aortic valve operation to a patient with a functioning LITA to the occluded left anterior descending artery and a GEA to the right coronary artery (RCA) by using a temporary vein graft to the RCA for the infusion of cardioplegic solution in addition to the conventional antegrade and retrograde cardioplegic infusions with ice slush topical cooling.